PEMBENTUKAN KALUS DAN EMBRIOGENESIS KULTUR PELEPAH DAUN DAN DAUN Caladium HIBRIDA - Irawati Irawati (Research Center for Biology-Indonesian Institute of Sciences, 2005)
Petiole and leaf cultures of Caladium hybrid were grown on MS medium+ lppm 2,4-D and transplanted to MS medium + 1 ppm NAA and then were grown on MS media with or without Kinetin and NAA.The greatest capacity of explants to produce callus was from the base cut and the top cut of the petioles as well as from the main vein of the leaf. Compact calli were grew further into adventive buds and plantlets.Through Scanning Electron Microscope,the development of adventive buds were observed grew from the parenchymatous cells and the vascular bundles.